Improving Students’ Speaking Ability through the Use of Holistic Method - Gunawan Gunawan; Abdul Rahman; Dian Riani Said; Fahriadi Muhdar (Universitas Cokroaminoto Palopo, 2024)
Speaking is like the first assessment for each learner who is studying English and each learner has to speak. This statement means an obligation, duty, task, fact, implementation, process, and it can be learning, although we still find some students are speaking little or even passive in the classroom. One of the method that can raise the students motivate in learning speaking is Holistic method. This study aims to identify the students’ improvement in speaking ability using Holistic Method. This research following the principle working of Classroom Action Research (CAR) that contained of four stages (Planning, Implementation, Observation, and Reflection). a classroom action research was applied by implementing two cycles and each cycle was applied four meetings. To increase the speaking proficiency and fluency of the SMP Negeri 6 Watampone, VII-B class, a holistic approach was used. The research findings indicated a significant improvement of the students’ speaking ability after implementing two cycles. About the speaking accuracy, the students’ get 56.50% in the Diagnostic test, 64.10% in cycle I, and 75.30% in the cycle II. About the speaking fluency, the students get 57.00% in the Diagnostic test, 65.50% in the cycle I, and 75.80% in the cycle II. In the second cycle, the pupils' speaking accuracy improved by 35.32%. In the second cycle, there was a 33.03% improvement in the pupils' speaking fluency. Consequently, the investigator came to the conclusion that the pupils in VII-B class at SMP Negeri 6 Watampone's usage of a holistic approach had been successful in improving their speaking abilities.